100 Most Influential Publications in Scoliosis Surgery. Issue 5 (March 2017) - Zhou, James Jun; Koltz, Michael T.; Agarwal, Nitin; Tempel, Zachary J.; Kanter, Adam S.; Okonkwo, David O.; Hamilton, D. Kojo
Abstract : Study Design: Bibliometric analysis. Objective: To apply the established technique of citation analysis to identify the 100 most influential articles in scoliosis surgery research published between 1900 and 2015. Summary of Background Data: Previous studies have applied the technique of citation analysis to other areas of study. This is the first article to apply this technique to the field of scoliosis surgery. Methods: A two-step search of the Thomson Reuters Web of Science was conducted to identify all articles relevant to the field of scoliosis surgery. The top 100 articles with the most citations were identified based on analysis of titles and abstracts. Further statistical analysis was conducted to determine whether measures of author reputation and overall publication influence affected the rate at which publications were recognized and incorporated by other researchers in the field. Results: Total citations for the final 100 publications included in the list ranged from 82 to 509. The period for publication ranged from 1954 to 2010. Most studies were published in the journal Spine (n = 63). The most frequently published topics of study were surgical techniques (n = 35) and outcomes (n = 35). Measures of author reputation (number of total studies in the top 100, number of first-author studies in the top 100) were found to have no effect on the rate at which studies were adopted by other researchers (number of years until first citation, and number of years until maximum citations). The number of citations/year a publication received was found to be negatively correlated with the rate at which it was adopted by other researchers, indicating that more influential manuscripts attained more rapid recognition by the scientific community at large. Conclusion: In assembling this publication, we have strived to identify and recognize the 100 most influential articles in scoliosis surgery research from 1900 to 2015. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text